The Effect Of Using Leaf Media To Improve Fine Motor Skills Of 4-5 Year Old Children At RA Smart Hafizh School Batam City - Alif Laini; Nurhayati, Nurhayati; Ayu Citra Dewi; Selpi Indramaya (Cita konsultindo, 2024)
The problem raised in this study is the effect of using leaf media in improving children's fine motor skills at RA Smart Hafizh School Batam City. The purpose of this study was to determine the effect of using leaf media in improving children's fine motor skills at RA Smart Hafizh School Batam City. In this study, researchers used a type of quantitative research with an experimental method that was